Financial strategy of small and medium businesses on the creative industry in Bandung, Indonesia. (10th May 2019) - Kostini, Nenden; Raharja, Sam'un Jaja
The role of small and medium enterprises (SMEs) is one aspect that encourages economic growth and development, whilst SMEs in the creative industry sector are important income generators. However, SMEs in the creative industry in Bandung, Indonesia are facing problems in terms of corporate finance. This study uses descriptive analysis as the research method and aims to formulate financial strategies that can be used by SMEs. The financial strategies for SMEs in the creative industry include as follows based on strength, weakness, opportunities and threat analysis: communicating with the relevant stakeholders, following partnership programs, improving and developing financial management and records, settling financial obligations and safeguarding the trust of the creditor and using loans for venture capital.